Cold-induced enhancement of avian uncoupling protein expression, heat production, and triiodothyronine concentrations in broiler chicks - Collin, A.; Buyse, J.; van As, P.; Darras, V. M.; Malheiros, R. D.; Moraes, VMB; Reyns, G. E.; Taouis, M.; Decuypere, E. (Elsevier B.V., 2003)
The relationships among avian uncoupling protein (avUCP) mRNA expression, heat production, and thyroid hormone metabolism were investigated in 7-14-day-old broiler chicks (Gallus gallus) exposed to a low temperature (cold-exposed chicks, CE) or a thermoneutral temperature (TN). After 7 days of exposure, CE chicks exhibited higher heat production (+83%, P < 0.01), avUCP mRNA expression (+20%, P < 0.01), and circulating triiodothyronine (T-3) levels (+104%, P = 0.07) for non-statistically different body weights and feed intake between 3 and 7 days of exposure as compared to TN chicks. Plasma thyroxine (T-4) concentration was clearly decreased in CE chicks (-33%, P = 0.06). The lower hepatic inner-ring deiodination activity (-47%) and the higher renal outer-ring deiodination activity (+75%) measured in CE compared to TN chicks could partly account for their higher plasma T3 concentrations. This study describes for the first time the induction of avUCP mRNA expression by low temperature in chickens, as it has been previously shown in ducklings, and supports the possible involvement of avUCP in avian thermogenesis. (C) 2003 Elsevier B.V. (USA). All rights reserved.
Keywords: thermogenesis; deiodination; low ambient temperature; thermoregulation